Efeitos do laser de baixa intensidade em780nm sobre a performance muscular aeróbica de ratos em treinamento físico em esteira - Vieira, Wouber Hérickson de Brito (2004)
The purpose of this study was to evaluate relative the physiological adaptation the activities of enzymes Lactate Dehidrogenase LDH (glycolytic) e Citrate Synthase CS (oxidative) and to the Anaerobic Threshold (AT), to the exercise in treadmill in rats submitted to the photostimulation for low-intensity laser (780 ηm) in the main participant muscles of the march. Fifty-four male Wistar rats had been part of the study. These animals were divided in four groups: Two had remained in rest (1) GRC, being one of them irradied (2) GRL, and other two were submitted to an aerobic treadmill training program during 5 weeks and to a multistage treadmill test of increasing intensity (3) GEC, being one of them irradied (4) GEL. The irradiation for infra-red laser (780 ηm) was made daily in number of four (quadriceps, maximum glúteo, soleus, tibialis anterior) in each back leg of the animals, totalizing 8 applications for animal/day, using (dose, 3,8 J/cm2; power, 15 mW; time, 10 s, continuous) during 5 weeks consecutives. The multistage treadmill tests of increasing intensity were made once a week totalizing 5 evaluation, in order to obtain blood samples for determination of the AT. In the analyses electrophoretics and spectrophotometic of the LDH and CS muscles samples (soleus, TA and cardiac) were removed 48 hours after the last exercise bout. The laser to promote increase in the oxidative metabolism of 2% a 78%, the exercise of 18% a 75%, and action combined of 43% a 92%; Apparent systemic action of the laser was detected in cardiac muscle with increase in the activity of the CS and reduction of the LDH. The group GEC and GEL showed increase in the maximum speed, in the speed corresponding to the AT and a trend reduction of the blood lactate concentration during the training period. However, no significant difference occurred between two groups though the GEL had shown higher values. These data suggest that the aerobic treadmill-training partner to the low-intensity laser can to promote physiological adaptation in the direction of increase oxidative capacity in the animals, represented by increase of the CS, reduction of the LDH and by the higher degree of effort to reach the Anaerobic Threshold. This similarity has a utility therapeutic practical.